Analysis of Contact Line Short-circuit Current Thermal Effect of Electrified Railway - Jianshuai SHAO (机车电传动)
In order to study the thermal effect of railway contact line in passive short circuit and power failure, the temperature rise between the main circuit, the pantograph slide and the contact line of the catenary caused by short-circuit current was studied. Firstly, the calculation method of short circuit current and contact area of contact line under passive short circuit and power failure mode was introduced. Then, the calculation model of local thermal effect model was presented, which calculated the heat of contact line, the temperature rise between contact line and slide plate. The results show that the heat is greatly affected by the width of the contact surface and the contact force; there is a high probability that the contact line is damaged or even fused in short circuit operation near the traction substation;the new contact line is in danger of breaking contact line under the action of great tension.